NEW STANDARDS IN EU CONSUMER RIGHTS PROTECTION?THE NEW DIRECTIVE 2011/83/EU - Arndt Kunnecke (European Scientific Journal, ESJ, 2014)
In recent years, consumer law has come more and more into the focus of legislation within the EU. One of the EU’s key objectives, completing the final stage of the internal market, is to place consumer rights in the centre of it. Following the adaption of various consumer law measures for some decades, the EU had undertaken a thorough review of its consumer acquis. After years of consultations, the Consumer Rights Directive 2011/83/EU, which was supposed to set new standards of consumer protection, came into force and will have to be implemented by the Member States by 13 December 2013. Renouncing its principal practice of minimum harmonisation in the area of consumer law, i.e. allowing Member States on the basis of Directives to adopt more protective rules, the EU legislator now turned to a targeted full harmonisation approach by means of the Consumer Rights Directive, aiming at increasing the consumer protection across the EU by bringing together the currently distinct laws for distance selling and off-premises contracts as well as other types of consumer contracts in a single instrument. The article briefly introduces the background of the Directive and discusses the shift in means of harmonisation concepts. Then it analyses the scope, concepts and content of the Directive, which mainly brings considerable reforms in the areas of information requirements and the right of withdrawal. Taking into account the Directive’s improvements and shortcomings, it concludes the need for further harmonisation and a uniform and universally applicable set of European consumer rights.